Battery cell and electric device

CN122950550APending Publication Date: 2026-10-20CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510453114.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-11
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

随着市场对电池单体在电性能方面的追求,电池单体的加工难度增大、良品率下降,导致电池单体的安全性能和使用寿命无法达到预期,限制了电池的进一步应用

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005354896680000221
    Figure BDA0005354896680000221
  • Figure BDA0005354896680000231
    Figure BDA0005354896680000231
  • Figure BDA0005354896680000241
    Figure BDA0005354896680000241
Patent Text Reader

Abstract

This application provides a single battery cell, comprising a positive electrode sheet, which includes a positive current collector, a positive electrode film layer disposed on at least one side of the positive current collector, and a base coating layer located between the positive current collector and the positive electrode film layer on at least one side. The positive electrode film layer comprises polycrystalline particles, and the base coating layer comprises first single-crystal particles with a volumetric particle size Dv99 less than or equal to 16 μm. The battery cell provided by this application exhibits excellent energy density and safety performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery cell technology, and in particular to a battery cell and an electrical device. Background Technology

[0002] In recent years, battery cells have been widely used in energy storage systems such as hydropower, thermal power, wind power, and solar power plants, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace, and many other fields. However, as the market demands higher electrical performance from battery cells, the processing difficulty has increased, and the yield rate has decreased. This has resulted in the safety performance and lifespan of battery cells failing to meet expectations, limiting their further application. How to simultaneously address both aspects has become a pressing issue in this field. Summary of the Invention

[0003] This application was made in view of the aforementioned issues and aims to at least solve one of the technical problems existing in the prior art. Therefore, this application provides a battery cell and an electrical device.

[0004] The first aspect of this application provides a battery cell, the battery cell including a positive electrode sheet, characterized in that the positive electrode sheet includes a positive current collector, a positive electrode film layer disposed on at least one side of the positive current collector, and a base coating layer located between the positive current collector and the positive electrode film layer on at least one side, wherein the positive electrode film layer includes polycrystalline particles, and the base coating layer includes first single crystal particles, the first single crystal particles having a volume distribution particle size Dv99 less than or equal to 16 μm.

[0005] Polycrystalline particles are agglomerations of small single-crystal particles, containing numerous grain boundaries and a large specific surface area, thus offering greater potential for specific capacity utilization. Including polycrystalline particles in the positive electrode film can effectively improve the energy density of individual battery cells. However, the high hardness and large particle size of polycrystalline particles, while increasing battery energy density, also exacerbate burr problems. Burred electrode sheets are prone to causing abnormal self-discharge of the cell after battery assembly, affecting battery safety performance.

[0006] In the battery cell provided in this application embodiment, by setting a base coating layer comprising single-crystal particles with a Dv99 value of less than or equal to 16 μm, the small particles can buffer the compression of the positive electrode current collector by large particles in the positive electrode film layer, which helps to reduce the generation of burrs. Simultaneously, in the battery cell provided in this application embodiment, while reducing the probability of burrs being generated in the current collector under the compression of large particles in the base coating layer and positive electrode film layer, high energy density can also be maintained, which is beneficial to the overall improvement of the battery cell's safety performance and energy density.

[0007] In any embodiment, the volume distribution particle size Dv99 of the first single crystal particle is 5μm-16μm, and can be selected as 6μm-13μm.

[0008] The undercoat, comprising small-diameter single-crystal particles within the aforementioned range, can effectively reduce burr formation. However, excessively small particles in the undercoat cannot achieve good particle size distribution, hindering the improvement of compaction density and thus deteriorating battery energy density. A volume distribution particle size Dv99 of the first single-crystal particle in the undercoat, meeting the aforementioned range, can effectively reduce the probability of burr formation while also mitigating the negative impact on battery energy density.

[0009] In any embodiment, the volume distribution particle size Dv50 of the first single crystal particle is 1μm-10μm, and can be selected as 1μm-6μm.

[0010] The monocrystalline particles in the bottom coating have a more compact crystal structure, smaller grain boundaries, and smaller specific surface area. During charging and discharging, they exhibit less slippage along the (003) crystal plane, resulting in a higher oxygen release temperature at high SOC levels, which is beneficial for improving the safety performance of the battery cell. However, if the particle size of the monocrystalline particles is too small, their specific surface area and the probability of side reactions with the electrolyte will increase, which is detrimental to improving battery safety performance. Controlling the volume distribution particle size Dv50 of the first monocrystalline particles in the bottom coating to meet the above-mentioned range reduces the probability of burrs generated during electrode cutting and further improves the safety performance of the battery cell.

[0011] In any embodiment, the thickness of the base coating on one side is 7μm-30μm, and can be selected as 10μm-25μm.

[0012] By placing an undercoat layer between the positive electrode film and the positive electrode current collector, the contact between the active material and the current collector can be effectively reduced, lowering the probability of burrs forming on the electrode sheet during slitting. However, if the thickness of the undercoat layer, including small particles, is too large, it will lead to a decrease in electrode compaction, negatively impacting the battery's energy density. If the thickness of the undercoat layer is too small, large particles in the positive electrode film will still compress the current collector, generating burrs, which is detrimental to improving battery safety performance. In the embodiments of this application, controlling the thickness of the undercoat layer on one side to meet the above-mentioned range can, on the one hand, effectively reduce the contact between large particles of the positive electrode active material and the current collector, reducing the probability of burrs forming on the electrode sheet during slitting and further improving the safety performance of the battery cell; on the other hand, it can simultaneously reduce the deterioration of electrode compaction and battery capacity loss caused by adding the undercoat layer, allowing the battery cell to still have a high energy density.

[0013] In any embodiment, the volume distribution particle size Dv50 of the polycrystalline particles is 5μm-15μm; and / or, the volume distribution particle size Dv99 of the polycrystalline particles is 10μm-30μm.

[0014] In any embodiment, the positive electrode film layer further includes a second single crystal particle.

[0015] In any embodiment, the volume distribution particle size Dv50 of the second single crystal particle is 1μm-10μm; and / or, the volume distribution particle size Dv99 of the second single crystal particle is 4μm-20μm.

[0016] The use of polycrystalline particles and second single-crystal particles that meet the above-mentioned particle size range in the positive electrode film layer is beneficial to improve the particle gradation, realize the close packing of particles in the positive electrode film layer, further improve the compaction density of the electrode sheet, and thus further improve the energy density of the battery.

[0017] In any embodiment, based on the total mass of the polycrystalline particles and the second single-crystal particles in the positive electrode film layer, the mass ratio of the polycrystalline particles is 50%-90%, and optionally 60%-80%.

[0018] In any embodiment, based on the total mass of the polycrystalline particles and the second single-crystal particles in the positive electrode film layer, the mass percentage of the second single-crystal particles is 10%-50%, optionally 20%-40%.

[0019] Controlling the mass ratio of polycrystalline particles and second monocrystalline particles in the positive electrode film to meet the above range, and increasing the proportion of polycrystalline particles in the positive electrode film, is beneficial to further improve the compaction density of the electrode sheet, so that the battery has excellent energy density.

[0020] In any embodiment, the thickness of the positive electrode film layer on one side is 40μm-120μm, and can be selected as 70μm-110μm.

[0021] Reducing the thickness of the positive electrode film helps to shorten the diffusion path of lithium ions and improve the dynamic performance of the battery cell. However, with the reduction of the positive electrode film thickness, in order to achieve high energy density, the compaction density of the electrode sheet is further increased, making the current collector more severely compressed by large particles during slicing, and increasing the probability of burr formation. At the same time, with the reduction of the thickness of the positive electrode film and the positive electrode sheet, the control level of large-size burrs is also tightened, and burrs are more likely to protrude from the edge of the positive electrode film, exacerbating the safety hazards of burr problems.

[0022] In any embodiment, the base coating layer includes a first positive electrode active material, and the positive electrode film layer includes a second positive electrode active material, wherein the first positive electrode active material and the second positive electrode active material each independently include Li. a1 Ni x1 Co y1 M1 z1 M2 w1 O 2-b1Wherein, M1 includes one or more of Mn and Al, and M2 includes one or more of Zr, B, Mg, Ti, W, Mo, Nb, Ta, Sr, Sb, and K; 0.8≤a1≤1.2, 0≤x1≤1, 0≤y1≤1, 0≤z1≤1, 0≤w1≤0.1, and -0.1≤b1≤0.1.

[0023] When the positive electrode film and the undercoat layer include the above-mentioned lithium-containing transition metal oxides, it is beneficial to the utilization of their specific capacity, thereby further improving the energy density of the battery cell.

[0024] In any embodiment, the first positive electrode active material includes nickel, and the molar percentage of nickel in the first positive electrode active material is 80%-96% based on the total number of moles of transition metals in the first positive electrode active material; and / or the second positive electrode active material includes nickel, and the molar percentage of nickel in the second positive electrode active material is 80%-96% based on the total number of moles of transition metals in the second positive electrode active material.

[0025] The bottom coating contains a first positive electrode active material with nickel content of 80%-96%. This can reduce the generation of burrs and the negative impact on battery capacity caused by the amount of positive electrode film occupied. It is beneficial to the utilization of the specific capacity of the electrode active material and further improves the energy density of the battery.

[0026] When the molar percentage of nickel in the second positive electrode active material in the positive electrode film is 80%-96%, it is beneficial to further improve the energy density of the battery cell. However, the high nickel content of the second positive electrode active material also results in high particle hardness, which exacerbates the compression of the current collector by large particles in the positive electrode film, making it easy to generate burrs during the positive electrode sheet cutting process. The technical solution in the embodiments of this application is particularly suitable for this positive electrode sheet, which improves the yield rate during the electrode sheet cutting process while further improving the high energy density of the battery, thus meeting the performance and efficiency requirements.

[0027] In any embodiment, when the battery cell is fully discharged, the compaction density of the positive electrode sheet is 3.4 g / cm³. 3 -3.65g / cm 3 .

[0028] The compaction density of the positive electrode sheet within the above range is beneficial to improving the yield rate during the electrode sheet cutting process while maintaining the high energy density of the battery cell, thus meeting performance and efficiency requirements.

[0029] A second aspect of this application provides an electrical device comprising a battery cell according to the first aspect of this application. Attached Figure Description

[0030] Figure 1This is a polished electron microscope image of a cross-section of a positive electrode sheet cut along the thickness direction according to one embodiment of this application;

[0031] Figure 2 This is a polished electron microscope image of the cross-section of the positive electrode sheet cut along the thickness direction in the comparative example of this application;

[0032] Figure 3 This is a front view of the positive electrode film layer of a positive electrode sheet cut along the thickness direction in one embodiment of this application;

[0033] Figure 4 This is a front view of the positive electrode film layer of the positive electrode sheet cut along the thickness direction in the comparative example of this application;

[0034] Figure 5 This is a comparison diagram of the oxygen release temperature of the positive electrode sheet in one embodiment and the comparative example of this application;

[0035] Figure 6 This is a schematic diagram of a battery cell according to one embodiment of this application;

[0036] Figure 7 yes Figure 6 An exploded view of a battery cell according to an embodiment of this application is shown.

[0037] Figure 8 This is a schematic diagram of a battery module according to one embodiment of this application;

[0038] Figure 9 This is a schematic diagram of a battery pack according to one embodiment of this application;

[0039] Figure 10 yes Figure 9 An exploded view of a battery pack according to one embodiment of this application is shown;

[0040] Figure 11 This is a schematic diagram of an electrical device in which a single battery cell is used as a power source according to one embodiment of this application.

[0041] Explanation of reference numerals in the attached figures:

[0042] 11 Positive electrode sheet; 111 Positive current collector; 112 Base coating; 113 Positive film layer;

[0043] 1121 First single crystal particle; 1131 Polycrystalline particle; 1132 Second single crystal particle;

[0044] 1 Battery pack; 2 Upper housing; 3 Lower housing; 4 Battery module; 5 Battery cell; 51 Housing; 52 Electrode assembly; 53 Top cover assembly. Detailed Implementation

[0045] The following detailed description, with appropriate reference to the accompanying drawings, discloses embodiments of the battery cell and power supply device of this application. However, unnecessary details may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of essentially the same structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided for the purpose of enabling those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.

[0046] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0047] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.

[0048] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.

[0049] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0050] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0051] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0052] As market demands for extended battery life increase, increasing the volumetric energy density of individual battery cells has become a common pursuit in the industry. Improving the volumetric energy density of individual battery cells often requires increasing the compaction density of the electrode sheets to increase the loading of active material per unit volume. However, researchers have found that high-compaction-density electrodes are prone to generating burrs during the cutting process. Burred electrodes are more likely to penetrate the separator after electrode assembly, causing abnormal self-discharge of the cell and even leading to short-circuit failure, thus affecting the battery's safety performance and lifespan, and failing to meet the usage requirements of individual battery cells.

[0053] [Battery cell]

[0054] Based on this, this application provides a battery cell, the battery cell including a positive electrode sheet, the positive electrode sheet including a positive current collector, a positive electrode film layer disposed on at least one side of the positive current collector, and a base coating layer located between the positive current collector and the positive electrode film layer on at least one side, wherein the positive electrode film layer includes polycrystalline particles, and the base coating layer includes first single crystal particles, the first single crystal particles having a volume distribution particle size Dv99 less than or equal to 16 μm.

[0055] In some implementations, such as Figure 1 As shown, the battery cell includes a positive electrode sheet 11, which includes a positive current collector 111, a positive electrode film layer 113 disposed on at least one side of the positive current collector, and a bottom coating layer 112 located between the positive current collector and the positive electrode film layer on at least one side. The positive electrode film layer includes polycrystalline particles 1131, and the bottom coating layer includes first single crystal particles 1121. The volume distribution particle size Dv99 of the first single crystal particles is 5μm-16μm.

[0056] In some embodiments, the volume distribution particle size Dv99 of the first single crystal particle is 5μm-16μm, and can be selected as 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, or any range between any two of the aforementioned values.

[0057] When used in this document, the term "burr" refers to a metal protrusion or bulge extending outward from the current collector, as specified in the IEEE 1725 standard for cell safety performance review and testing. The direction of extension can be any direction, such as the thickness direction or the electrode plane direction, and the causes include, but are not limited to, cutting, tearing, etc.

[0058] When used in this document, the terms "volume distribution particle size Dv99" and "Dv50" refer to the particle sizes corresponding to a cumulative volume distribution percentage of 99% and 50%, respectively. These values ​​can be determined using conventional instruments and methods in the field. For example, they can be determined using instruments employing the particle size distribution laser diffraction method (such as the Mastersizer 2000E laser particle size analyzer from Malvern Instruments Ltd., UK) in accordance with GB / T19077-2016.

[0059] The volumetric particle size Dv99 of the first single crystal in the base coating can be tested using any method known in the art. As an example, powder is scraped from the base coating and tested in accordance with the method described above.

[0060] When used in this article, the term "polycrystalline grain" refers to an aggregate of single-crystal grains. Here, the aggregation is a hard aggregation caused by chemical bonding of single-crystal grains, resulting in a large number of grain boundaries and inconsistent atomic orientations within the polycrystalline grain. After cutting the cross-section of the polycrystalline grain, it can be seen that the polycrystalline grain is formed by the aggregation of many single-crystal grains. However, due to chemical bonding, it is difficult to identify the specific size of the single-crystal grains inside the polycrystalline grain.

[0061] As used herein, the term "single-crystal particle" refers to the smallest unit of particle within a certain observation range. A single-crystal particle may contain defects of any form, but it is impossible to define smaller particles within it. It is understood that the single-crystal particle described herein does not necessarily mean that the single crystal lacks grain boundaries, or that atoms, molecules, or ions are arranged in a continuous and consistent periodic pattern in three-dimensional space. Rather, it refers to particles within a single crystal that cannot be defined by grain boundaries at a certain observation scale. The single-crystal particle referred to in this article refers to particles existing in the electrode sheet in the form of single-crystal particles, excluding single-crystal particles that constitute polycrystalline particles.

[0062] The positive electrode film includes polycrystalline particles, which are aggregates of small single-crystal particles. These particles have numerous grain boundaries, a large specific surface area, and greater potential for specific capacity utilization. Including polycrystalline particles in the positive electrode film can effectively improve the energy density of individual battery cells. However, the high hardness and large particle size of polycrystalline particles, while increasing battery energy density, can also exacerbate burr problems, such as… Figure 2 and Figure 3 As shown, electrode plates with burrs are prone to causing abnormal self-discharge of the battery cell after battery assembly, affecting the battery's safety performance.

[0063] In the battery cells provided in the embodiments of this application, such as Figure 1 and Figure 4 As shown, by setting a base coating layer comprising single-crystal particles with a Dv99 value of 16 μm or less, the small particles can buffer the compression of the positive electrode current collector by large particles in the positive electrode film layer, thus reducing the generation of burrs. Simultaneously, the battery cell provided in this application embodiment reduces the probability of burrs being generated in the current collector under the compression of large particles in the base coating layer and positive electrode film layer, while maintaining high energy density, which is beneficial to the overall improvement of the battery cell's safety performance and energy density.

[0064] In some embodiments, the volumetric particle size Dv99 of the first single crystal particle is 6μm-13μm.

[0065] In some embodiments, the volumetric particle size distribution (Dv50) of the first single crystal particle is 1 μm-10 μm. In some embodiments, the volumetric particle size distribution (Dv50) of the first single crystal particle is 1 μm-6 μm.

[0066] In some embodiments, the volume distribution particle size Dv50 of the first single crystal particle can be selected as 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, or any range between any two of the aforementioned values.

[0067] The monocrystalline particles in the bottom coating have a more compact crystal structure, smaller grain boundaries and specific surface area, and less slippage along the (003) crystal plane during charging and discharging. Therefore, they have a higher oxygen release temperature at high SOC, which is beneficial to improving the safety performance of the battery cell. The bottom coating includes first monocrystalline particles with a volume distribution particle size Dv50 that meets the above range, which reduces the probability of burrs generated during electrode cutting and further improves the safety performance of the battery cell.

[0068] In some embodiments, the thickness of the single-sided undercoat layer is 7 μm-30 μm. In some embodiments, the thickness of the single-sided undercoat layer is 10 μm-25 μm.

[0069] In some embodiments, the thickness of the single-sided undercoat layer can be selected as 7μm, 10μm, 12μm, 15μm, 18μm, 20μm, 22μm, 25μm, 28μm, 30μm, or any range between any two of the aforementioned values.

[0070] Adding an undercoat layer between the positive electrode film and the positive electrode current collector can effectively reduce the contact between polycrystalline particles in the positive electrode film and the current collector, reducing the probability of burrs forming on the electrode sheet during slitting. However, the addition of the undercoat layer occupies space in the positive electrode film, negatively impacting the battery's energy density. Controlling the thickness of the undercoat layer on one side to meet the above-mentioned range can effectively reduce the contact between large particles of the positive electrode active material and the current collector, reducing the probability of burrs forming on the electrode sheet during slitting and further improving the safety performance of the battery cell. On the other hand, since the specific capacity of small monocrystalline particles is lower than that of large particles in the positive electrode film, controlling the thickness of the undercoat layer on one side to meet the above-mentioned range can simultaneously reduce the deterioration of electrode compaction and battery capacity loss caused by adding the undercoat layer, allowing the battery cell to still have a high energy density.

[0071] In some embodiments, the volumetric particle size distribution (Dv50) of the polycrystalline particles is 5 μm-15 μm.

[0072] In some embodiments, the volume distribution particle size Dv50 of the polycrystalline particles can be selected as 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, or any range between any two of the aforementioned values.

[0073] In some embodiments, the volumetric particle size distribution (Dv99) of the polycrystalline particles is 10 μm-30 μm.

[0074] In some embodiments, the volume distribution particle size Dv99 of the polycrystalline particles can be selected as 10μm, 12μm, 15μm, 18μm, 20μm, 22μm, 25μm, 28μm, 30μm, or any range between any two of the aforementioned values.

[0075] In some embodiments, the positive electrode film layer also includes a second single-crystal particle, such as... Figure 1 As shown, the positive electrode film 113 includes a second single crystal particle 1132.

[0076] In some embodiments, the volumetric particle size Dv50 of the second single crystal particle is 1 μm-10 μm.

[0077] In some embodiments, the volume distribution particle size Dv50 of the second single crystal particle can be selected as 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, or any range between any two of the aforementioned values.

[0078] In some embodiments, the volumetric particle size Dv99 of the second single crystal particle is 4μm-20μm.

[0079] In some embodiments, the volume distribution particle size Dv99 of the second single crystal particle can be selected as 4μm, 6μm, 8μm, 10μm, 12μm, 14μm, 16μm, 18μm, 20μm, or any range between any two of the aforementioned values.

[0080] The use of polycrystalline particles and second single-crystal particles that meet the above-mentioned particle size range in the positive electrode film layer is beneficial to improve the particle gradation, realize the close packing of particles in the positive electrode film layer, further improve the compaction density of the electrode sheet, and thus further improve the energy density of the battery.

[0081] In this paper, the first single-crystal particles in the undercoat layer, the second single-crystal particles in the cathode film layer, and the polycrystalline particles in the cathode film layer can be measured by scanning electron microscopy.

[0082] In some embodiments, the mass percentage of the polycrystalline particles is 50%-90% based on the total mass of the second monocrystalline particles and the polycrystalline particles in the positive electrode film. In some embodiments, the mass percentage of the polycrystalline particles is 60%-80% based on the total mass of the second monocrystalline particles and the polycrystalline particles in the positive electrode film.

[0083] In some embodiments, based on the total mass of the second single crystal particle and the polycrystalline particle in the positive electrode film, the mass percentage of the polycrystalline particle can be selected as 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, or any range between any two of the aforementioned values.

[0084] In some embodiments, the mass percentage of the second single-crystal particle is 10%-50% based on the total mass of the second single-crystal particle and the polycrystalline particle in the positive electrode film. In some embodiments, the mass percentage of the second single-crystal particle is 20%-40% based on the total mass of the second single-crystal particle and the polycrystalline particle in the positive electrode film.

[0085] In some embodiments, based on the total mass of the second single crystal particle and the polycrystalline particle in the positive electrode film, the mass percentage of the second single crystal particle can be selected as 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, or any range between any two of the aforementioned values.

[0086] When used in this paper, the mass ratio of polycrystalline particles and second monocrystalline particles can be determined by the following method: Take a prepared positive electrode sheet, or a positive electrode sheet disassembled from a battery, and perform CP-SEM testing. Randomly select a number of points for imaging, with the number of points being ≥10 (e.g., 10, 20, 50, 100, etc.). Calculate the area ratio of the positive electrode film size occupied by polycrystalline particles and monocrystalline particles in the obtained images, and calculate the average value. The area ratio between polycrystalline particles and second monocrystalline particles can be equivalent to the mass ratio of polycrystalline particles and second monocrystalline particles.

[0087] Controlling the mass ratio of polycrystalline particles and second single-crystal particles in the positive electrode film to meet the above range is beneficial to further improve the compaction density of the electrode sheet, so that the battery has excellent energy density.

[0088] In some embodiments, the thickness of the positive electrode film on one side is 40 μm-120 μm. In some embodiments, the thickness of the positive electrode film on one side is 70 μm-110 μm.

[0089] In some embodiments, the thickness of the single-sided positive electrode film can be selected as 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 110μm, 120μm, or any range between any two of the aforementioned values.

[0090] Reducing the thickness of the positive electrode film helps to shorten the diffusion path of lithium ions and improve the dynamic performance of the battery cell. However, with the reduction of the positive electrode film thickness, in order to achieve high energy density, the compaction density of the electrode sheet is further increased, making the current collector more severely compressed by large particles during slicing, and increasing the probability of burr formation. At the same time, with the reduction of the thickness of the positive electrode film and the positive electrode sheet, the control level of large-size burrs is also tightened, and burrs are more likely to protrude from the edge of the positive electrode film, exacerbating the safety hazards of burr problems.

[0091] In some embodiments, the undercoat layer includes a first positive electrode active material, and the positive electrode film layer includes a second positive electrode active material, wherein the first positive electrode active material and the second positive electrode active material each independently include Li. a1 Ni x1 Co y1 M1 z1 M2 w1 O 2-b1 Wherein, M1 includes one or more of Mn and Al, and M2 includes one or more of Zr, B, Mg, Ti, W, Mo, Nb, Ta, Sr, Sb, and K; 0.8≤a1≤1.2, 0≤x1≤1, 0≤y1≤1, 0≤z1≤1, 0≤w1≤0.1, and -0.1≤b1≤0.1.

[0092] In some embodiments, a1 can be selected as 0.8, 0.85, 0.9, 0.95, 1.0, 1.05, 1.1, 1.15, 1.2, or any range between any two of the aforementioned values. In some embodiments, x1 can be selected as 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, or any range between any two of the aforementioned values. In some embodiments, y1 can be selected as 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, or any range between any two of the aforementioned values. In some embodiments, z1 can be selected as 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, or any range between any two of the aforementioned values. In some implementations, w1 can be selected as 0, 0.02, 0.04, 0.06, 0.08, 0.1, or any range between any two of the aforementioned values. In some implementations, b1 can be selected as -0.1, -0.05, 0, 0.05, 0.1, or any range between any two of the aforementioned values.

[0093] Lithium-containing transition metal oxides are an important class of cathode materials for lithium-ion batteries. They are characterized by the combination of transition metals (such as cobalt, nickel, and manganese) with oxygen to form layered or spinel structures, exhibiting excellent theoretical specific capacity and serving as crucial cathode active materials for high-energy-density batteries. Examples include, but are not limited to, lithium cobalt oxide (LiCoO2, LCO), lithium nickel oxide (LiNiO2, LNO), ternary materials such as lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide, and lithium-rich manganese-based oxides. Including these types of lithium-containing transition metal oxides in the cathode film and undercoat layer is beneficial for maximizing specific capacity, thereby further improving the energy density of the battery cell.

[0094] It is understandable that the composition of the first positive electrode active material and the second positive electrode active material can be the same or different.

[0095] It is understandable that the first single-crystal particles in the base coating mainly originate from the first positive electrode active material, while the second single-crystal particles and polycrystalline particles in the positive electrode film mainly originate from the second positive electrode active material.

[0096] In some embodiments, the first positive electrode active material includes nickel, and the molar percentage of nickel in the first positive electrode active material is 80%-96% based on the total number of moles of transition metals in the first positive electrode active material.

[0097] In some embodiments, based on the total number of moles of transition metals in the first positive electrode active material, the molar percentage of nickel in the first positive electrode active material can be selected as 80%, 82%, 84%, 86%, 88%, 90%, 92%, 94%, 96%, or any range between any two of the aforementioned values.

[0098] In this document, the molar percentage of nickel in the first positive electrode active material can be determined using instruments and methods known in the art. As an example, 0.5 g of the test material is scraped from the undercoat and immersed in 100 mL of aqua regia for digestion at 50°C. The completely dissolved solution is then subjected to inductively coupled plasma (ICP) testing to detect the content of transition metals (such as Ni, Co, Mn ions). The molar percentage of nickel in the first positive electrode active material is calculated by dividing the number of moles of nickel by the total number of moles of transition metals. It is understood that the material in the undercoat primarily originates from the first positive electrode active material.

[0099] The bottom coating contains a first positive electrode active material with nickel content of 80%-96%. This can reduce the generation of burrs and the negative impact on battery capacity caused by the amount of positive electrode film occupied. It is beneficial to the utilization of the specific capacity of the electrode active material and further improves the energy density of the battery.

[0100] In some embodiments, the second positive electrode active material includes nickel, and the molar percentage of nickel in the second positive electrode active material is 80%-96% based on the total number of moles of transition metals in the second positive electrode active material.

[0101] In some embodiments, based on the total number of moles of transition metals in the second positive electrode active material, the molar percentage of nickel in the second positive electrode active material can be selected as 80%, 82%, 84%, 86%, 88%, 90%, 92%, 94%, 96%, or any range between any two of the aforementioned values.

[0102] As used herein, the molar percentage of nickel in the second positive electrode active material within the positive electrode film can be determined using instruments and methods known in the art. As an example, powder is scraped from the positive electrode film, and the test is performed as described above.

[0103] When the molar percentage of nickel in the second positive electrode active material in the positive electrode film is 80%-96%, it is beneficial to further improve the energy density of the battery cell. However, the high nickel content of the second positive electrode active material also results in high particle hardness, which exacerbates the compression of the current collector by large particles in the positive electrode film, making it easy to generate burrs during the positive electrode sheet cutting process. The technical solution in the embodiments of this application is particularly suitable for this positive electrode sheet, which improves the yield rate during the electrode sheet cutting process while further improving the high energy density of the battery, thus meeting the performance and efficiency requirements.

[0104] In some embodiments, the cold-pressed compaction density of the positive electrode sheet is 3.1 g / cm³. 3 -3.8g / cm 3 3.1g / cm³ is an option. 3 3.2g / cm 3 3.3g / cm 3 3.4g / cm 3 3.5g / cm 3 3.6g / cm 3 3.7g / cm 3 3.8g / cm 3 , or any range between any two of the aforementioned values.

[0105] When used herein, the cold-pressed compaction density of the positive electrode sheet can be determined using instruments and methods known in the art. As an example, the following method can be used for testing: Take a positive electrode sheet prepared by cold pressing, weigh the electrode sample with an area of ​​S using an electronic balance, record the weight as W, and then measure the thickness T of the electrode sheet (this can be done using instruments conventionally available in the art capable of measuring electrode sheet thickness, including but not limited to a micrometer). The cold-pressed compaction density of the positive electrode sheet can be calculated using the formula W / (T×S).

[0106] In some embodiments, when the battery cell is fully discharged, the compaction density of the positive electrode sheet is 3.4 g / cm³. 3 -3.65g / cm 3 3.4g / cm³ is an optional value. 3 3.42 g / cm 3 3.45g / cm 3 3.48 g / cm 3 3.5g / cm 3 3.52g / cm 3 3.55g / cm 3 3.58g / cm 3 3.6g / cm 3 3.62g / cm 3 3.65g / cm3 , or any range between any two of the aforementioned values.

[0107] When used herein, the compaction density of the positive electrode sheet of the battery cell when fully discharged can be determined using instruments and methods known in the art. As an example, the following method can be used for testing: Place the battery cell at 25°C and let it stand for 2 hours. While maintaining the battery temperature at 25°C, discharge the battery at a constant current of 1 / 3C to 2.8V, let it stand for 30 minutes, and then discharge it at a constant current of 0.04C to 2.8V. Disassemble the electrode sheet when fully discharged, clean the residual electrolyte with an organic solvent (the organic solvent can be any solvent commonly used in the art capable of cleaning electrolytes, including but not limited to dimethyl carbonate), dry the electrode sheet after removing the residual electrolyte, and then determine the compaction density of the positive electrode sheet when fully discharged using the aforementioned method for measuring the cold-pressed compaction density of the positive electrode sheet.

[0108] The compaction density of the positive electrode sheet within the above range is beneficial to improving the yield rate during the electrode sheet cutting process while maintaining the high energy density of the battery cell, thus meeting performance and efficiency requirements.

[0109] [Positive electrode plate]

[0110] This application provides a positive electrode sheet, which includes a positive current collector, a positive electrode film layer disposed on at least one side of the positive current collector, and an undercoating layer located between the positive current collector and the positive electrode film layer on at least one side, wherein the positive electrode film layer includes a positive active material.

[0111] In some embodiments, the positive current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0112] In some embodiments, the positive electrode film layer and the base layer may optionally include a binder. As an example, the binder may include at least one selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.

[0113] In some embodiments, the positive electrode film and the undercoat may optionally include a conductive agent. As an example, the conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0114] In some embodiments, the positive electrode sheet can be prepared by dispersing the components used to prepare the base coating, such as the first positive electrode active material, conductive agent, binder and any other components, in a solvent (e.g., N-methylpyrrolidone) to form a base coating slurry; dispersing the second positive electrode active material, conductive agent, binder and any other components in a solvent to form a positive electrode slurry; firstly coating the base coating onto the positive electrode current collector, and after drying and other processes, coating the positive electrode film slurry onto the surface of the base coating, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0115] [Negative electrode plate]

[0116] The negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector, the negative electrode film layer including a negative electrode active material.

[0117] As an example, the negative electrode current collector has two surfaces opposite each other in its own thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.

[0118] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0119] In some embodiments, the negative electrode active material may be a negative electrode active material known in the art for use in batteries. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, this application is not limited to these materials, and other conventional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0120] In some embodiments, the negative electrode film layer may optionally include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0121] In some embodiments, the negative electrode film may optionally include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0122] In some embodiments, the negative electrode film may optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).

[0123] In some embodiments, the negative electrode sheet can be prepared by dispersing the components used to prepare the negative electrode sheet, such as the negative electrode active material, conductive agent, binder and any other components, in a solvent (e.g., deionized water) to form a negative electrode slurry; coating the negative electrode slurry onto the negative electrode current collector, and then obtaining the negative electrode sheet after drying, cold pressing and other processes.

[0124] [Electrolytes]

[0125] The electrolyte acts as a conductor of ions between the positive and negative electrode plates. This application does not specifically limit the type of electrolyte; it can be selected according to requirements. For example, the electrolyte can be liquid, solid, or gel-like.

[0126] In some embodiments, the electrolyte is an electrolyte solution. The electrolyte solution includes an electrolyte salt and a solvent.

[0127] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate, and lithium tetrafluorooxalate phosphate.

[0128] In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.

[0129] In some embodiments, the electrolyte may optionally include additives. For example, additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature or low-temperature performance, etc.

[0130] [Isolation membrane]

[0131] In some embodiments, the secondary battery also includes a separator. This application does not impose any particular limitation on the type of separator; any known porous separator with good chemical and mechanical stability can be selected.

[0132] In some embodiments, the material of the separator can be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0133] In some implementations, the positive electrode, negative electrode, and separator can be fabricated into an electrode assembly using a winding or stacking process.

[0134] In some embodiments, the battery cell may include an outer packaging. This outer packaging can be used to encapsulate the electrode assembly and electrolyte described above.

[0135] In some embodiments, the outer packaging of the battery cell can be a rigid shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging of the battery cell can also be a flexible package, such as a pouch. The material of the flexible package can be plastic; examples of plastics include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0136] This application does not impose any particular limitation on the shape of the battery cell; it can be cylindrical, square, or any other arbitrary shape. For example, Figure 6 The example shown is a square-structured battery cell 5.

[0137] In some implementations, refer to Figure 7 The outer packaging may include a housing 51 and a cover plate 53. The housing 51 may include a base plate and side plates connected to the base plate, the base plate and side plates forming a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the cover plate 53 can be placed over the opening to close the receiving cavity. The positive electrode sheet, negative electrode sheet, and separator can be formed into an electrode assembly 52 by a winding process or a stacking process. The electrode assembly 52 is encapsulated within the receiving cavity. Electrolyte is immersed in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in a single battery cell 5 can be one or more, which can be selected by those skilled in the art according to specific practical needs.

[0138] In some implementations, individual battery cells can be assembled into a battery module. The number of individual battery cells contained in a battery module can be one or more, and the specific number can be selected by those skilled in the art based on the application and capacity of the battery module.

[0139] Figure 8 This is battery module 4, used as an example. (See reference...) Figure 8 In battery module 4, multiple battery cells 5 can be arranged sequentially along the length of battery module 4. Of course, they can also be arranged in any other manner. Furthermore, these multiple battery cells 5 can be fixed in place using fasteners.

[0140] Optionally, the battery module 4 may also include a housing with a receiving space in which multiple battery cells 5 are received.

[0141] In some embodiments, the battery modules described above can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be one or more, the specific number of which can be selected by those skilled in the art according to the application and capacity of the battery pack.

[0142] Figure 9 and Figure 10 This is battery pack 1 as an example. (See reference...) Figure 9 and Figure 10 The battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box includes an upper body 2 and a lower body 3, with the upper body 2 covering the lower body 3 to form a closed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.

[0143] In addition, this application also provides a battery device, including the battery cell provided in the first aspect of this application, wherein the battery device includes at least one of a battery module, a battery pack, and an energy storage battery.

[0144] In addition, this application also provides an electrical device, which includes the battery cell provided in the first aspect of this application. The battery cell, battery module, or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.

[0145] As the electrical device, a single battery cell, a battery module, or a battery pack can be selected according to its usage requirements.

[0146] Figure 11 This is an example of an electrical device. The device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of individual battery cells, a battery pack or battery module can be used.

[0147] Another example device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use a single battery cell as their power source.

[0148] Example

[0149] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.

[0150] I. Preparation Method

[0151] Example 1

[0152] 1) Preparation of positive electrode sheet

[0153] Preparation of the base coating slurry: The first positive electrode active material LiNi 0.92 Co 0.04 Mn 0.04 The first single crystal particles of O2 (9μm for Dv99 and 4μm for Dv50), conductive carbon, and PVDF binder are mixed at a mass ratio of 98:1:1. N-methyl-2-pyrrolidone (NMP) solvent is added, and the mixture is stirred under vacuum until the system is homogeneous to obtain the base coating slurry.

[0154] Preparation of positive electrode film slurry: The second positive electrode material, LiNi... 0.92 Co 0.04 Mn 0.04 A mixture of polycrystalline O2 particles (Dv99: 25μm, Dv50: 8μm) and second single-crystal particles (Dv99: 12μm, Dv50: 5μm) (mass ratio of polycrystalline particles to second single-crystal particles: 7:3), conductive carbon, and binder PVDF are mixed at a mass ratio of 98:1:1. Solvent NMP is added, and the mixture is stirred under vacuum until the system is homogeneous to obtain the positive electrode film slurry.

[0155] The primer coating slurry is evenly coated on both sides of the positive electrode current collector and then dried to form the primer coating, wherein the coating weight on one side is 3.65 mg / cm². 2The positive electrode film slurry was uniformly coated on the surface of the undercoat layer away from the positive electrode current collector, with a single-sided coating weight of 12.55 mg / cm². 2 After being air-dried at room temperature, the material is transferred to an oven for further drying, and then cold-pressed to obtain the positive electrode sheet.

[0156] Electrode slitting (one out of two): The positive electrode is slitting on a slitting machine at a speed of 0.5 m / s. The slitting blade is made of steel and the negative pressure of the slitting machine is -10 kPa.

[0157] Electrode cutting: The slit electrode sheets are wound and cut, with a winding speed of 0.6m / s, a core length of 3m, and a steel cutting blade. The winding machine is under a negative pressure of -10Kpa.

[0158] 2) Preparation of negative electrode sheet

[0159] Artificial graphite (anode material), polyvinyl alcohol (binder), and SP-Li (conductive agent) were thoroughly mixed and ball-milled in a deionized water solvent system at a mass ratio of 90:5:5 to obtain anode slurry. The anode slurry was then subjected to a concentration of 23.8 mg / cm³. 2 The single-sided coating weight is applied to the copper foil surface and vacuum dried overnight at 110°C to obtain the negative electrode sheet.

[0160] 3) Preparation of the diaphragm

[0161] A polyethylene film with a thickness of 13 μm was used as the separator.

[0162] 4) Preparation of electrolyte

[0163] Lithium hexafluorophosphate (LiPF6) was dissolved in ethylene carbonate (EC), diethyl carbonate (DEC), and dimethyl carbonate (DMC) in a volume ratio of 1:1:1 to form a homogeneous solution, thus obtaining an electrolyte with a LiPF6 concentration of 1 mol / L.

[0164] 5) Battery assembly

[0165] The electrodes are arranged in the order of "separator-negative electrode-separator-positive electrode". One end of the positive electrode, negative electrode, and two separators is fixed to the discharge roller, and the other end is stacked together and fixed to the winding shaft. A motor is used to rotate the winding shaft to wind the positive electrode, negative electrode, and two separators, resulting in a wound bare cell. The bare cell is placed in an outer packaging, injected with the electrolyte, and sealed to obtain a battery cell.

[0166] The thickness of the single-sided bottom coating is 10 μm, the thickness of the single-sided positive electrode film is 34.4 μm, and the cold-pressed compaction density of the positive electrode sheet is 3.65 g / cm³. 3 ;

[0167] Examples 2-6

[0168] The battery cells of Examples 2-6 are prepared in a similar manner to those of Example 1, except that the volume distribution particle sizes Dv99 and Dv50 of the first single crystal particles in the base coating are changed, as detailed in Table 1.

[0169] Examples 7-8

[0170] The battery cells of Examples 7-8 are prepared in a similar manner to the battery cells of Example 1, except that the thickness of the bottom coating on one side is changed, as detailed in Table 1.

[0171] Examples 9-12

[0172] The battery cells of Examples 9-12 are prepared in a similar manner to the battery cells of Example 1, except that the volume distribution particle sizes Dv99 and Dv50 of the polycrystalline particles and the second single crystal particles in the positive electrode film are changed, as shown in Table 1.

[0173] Examples 13-14

[0174] The battery cells of Examples 13-14 are prepared in a similar manner to the battery cells of Example 1, except that the mass ratio of polycrystalline particles to second single-crystal particles in the positive electrode film is changed, as shown in Table 1.

[0175] Comparative Example 1

[0176] The battery cell of Comparative Example 1 is prepared in a similar manner to the battery cell of Example 1, except that the preparation of the base coating is changed and the base coating is not included, as detailed in Table 1.

[0177] Comparative Example 2

[0178] The battery cells of Comparative Examples 2-3 are prepared in a similar manner to the battery cells of Example 1. The difference is that the volume distribution particle size Dv99 of the first single crystal particles in the bottom coating is changed, and Dv99 does not meet the requirement of being less than or equal to 16 μm, as shown in Table 1.

[0179] Table 1 Preparation parameters

[0180]

[0181]

[0182] II. Performance Testing

[0183] 1. CP-SEM characterization method for cross-section of positive electrode sheet

[0184] The sample to be characterized was prepared as follows: First, the positive electrode sheet was cut into a 2cm × 2cm sample and fixed on the sample stage with paraffin wax. Then, the sample stage was installed in the sample holder and locked in place. The power supply of the IB-19500CP argon ion cross-section polisher was turned on and a vacuum was drawn. The argon flow rate was set to 0.15 MPa, the control voltage to 8 kV, and the polishing time to 2 hours. The sample stage was adjusted to the swing mode to start polishing. After polishing, the sample to be characterized was obtained.

[0185] Microscopic morphology characterization: The samples were characterized using a ZEISS Sigma300 scanning electron microscope. Sample testing can be performed according to JY / T010-1996. To ensure the accuracy of the test results, multiple different regions were randomly selected from the sample for scanning tests, and cross-sectional morphology images were taken at a fixed magnification of 5kx.

[0186] 2. Test method for particle size of materials in positive electrode plates

[0187] The battery cells were disassembled, and the powder to be tested was scraped out from the base coating. The test material was poured into an air dispersion tank containing ethanol and ultrasonically dispersed for 5 minutes. Sodium dodecyl sulfate (SDS) was added as a dispersant. Then, it was loaded into a laser particle size analyzer (Malvin 2000E) for testing to obtain the volume distribution particle size of the first single crystal particles in the base coating.

[0188] Disassemble the battery cell and obtain the CP-SEM spectrum of the positive electrode using the method described above. Randomly select 10 different electrode regions and label the size of the polycrystalline particles and the second monocrystalline particles in the positive electrode film. Calculate Dv99 and Dv50 based on the volume particle size distribution and obtain their average values ​​as Dv99 and Dv50 of the polycrystalline particles and the second monocrystalline particles in the positive electrode film.

[0189] 3. Characterization method for burr testing on the cross-section of the positive electrode sheet

[0190] The slit electrodes were characterized using a super depth-of-field microscope (Keyence 600). The test temperature was 25℃, the size of the test electrode was 80mm×60mm, the magnification was 300x, and the light-gathering aperture was 30%. The burrs were observed and the dimensions were calibrated from the slit cross section of the electrode.

[0191] Burr size statistics: By observing 2000 slit electrodes with CCD, the frequency K1 of electrodes with burrs was counted, and the burr ratio was calculated to be K1 / 2000×100%.

[0192] 4. DSC test method for the safety performance of the positive electrode sheet

[0193] The prepared positive electrode sheet or the positive electrode sheet disassembled from the battery cell is placed in a DSC crucible, under N2 atmosphere, with a heating rate of 10℃ / min and a temperature range of 25℃-800℃, and its peak decomposition temperature is tested.

[0194] 5. Energy density of a single battery cell

[0195] The weight M of all active materials loaded per unit area on the positive electrode of each battery cell is measured, and the cell volume is V. Each battery is charged at room temperature at a rate of 0.33C to a voltage of 4.25V, and then discharged at a rate of 0.33C to a voltage of 2.8V. The discharge energy S0 is measured, and the cell volumetric energy density is obtained as S0 / V.

[0196] III. Analysis of Test Results for Each Embodiment and Comparative Example

[0197] Battery cells for each embodiment and comparative example were prepared according to the above method, and various performance parameters were measured. The results are shown in Tables 2 and 3 below.

[0198] Table 2 Performance Parameters

[0199]

[0200]

[0201] As can be seen from the comparison of the embodiments and comparative examples in Table 2, the positive electrode film layer of the positive electrode sheet of the battery cell includes polycrystalline particles and the bottom coating layer includes first single crystal particles. The volume distribution particle size Dv99 of the first single crystal particles is less than or equal to 16μm, which can effectively reduce the probability of burrs generated during electrode sheet cutting, and at the same time enable the battery cell to have excellent energy density and safety performance.

[0202] Table 3 Preparation or performance parameters

[0203]

[0204] As can be seen from the comparison of Examples 1-6 in Table 3, the volume distribution particle size Dv99 of the first single crystal particles in the bottom coating of the positive electrode of the battery cell is 5μm-16μm, and Dv50 is 1μm-10μm. The battery cell has high energy density, low burr ratio, and high oxygen release temperature, which is beneficial to improving the safety performance of the battery cell. Furthermore, the volume distribution particle size of the first single crystal particles is 6μm-13μm and Dv50 is 1μm-6μm, which can further improve the safety performance of the battery cell.

[0205] As can be seen from the comparison of Examples 1 and 7-8 in Table 2, the thickness of the bottom coating on one side of the positive electrode of the battery cell is 7μm-30μm, which can reduce the probability of electrode burr generation and reduce battery capacity loss, so that the battery cell has a high energy density.

[0206] As can be seen from the comparison of Examples 1 and 9-12 in Table 2, the volume distribution particle size Dv50 of the polycrystalline particles in the positive electrode film layer is 5μm-15μm and Dv99 is 10μm-30μm, while the volume distribution particle size Dv50 of the second single crystal particles is 1μm-10μm and Dv99 is 4μm-20μm. This is beneficial to improve the particle gradation in the positive electrode film layer, achieve close packing of particles, and enable the battery cell to have high energy density.

[0207] As can be seen from the comparison of Examples 1 and 13-14 in Table 2, in the positive electrode sheet, based on the total mass of the second monocrystalline particles and the polycrystalline particles in the positive electrode film layer, the mass ratio of polycrystalline particles is 50%-90%, and the mass ratio of the second monocrystalline particles is 10%-50%, which is beneficial to improve the compaction density of the positive electrode sheet, thereby improving the energy density of the battery cell.

[0208] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

Claims

1. A battery cell, said battery cell comprising a positive electrode, characterized in that, The positive electrode includes a positive current collector, a positive electrode film layer disposed on at least one side of the positive current collector, and a base coating layer located between the positive current collector and the positive electrode film layer on at least one side. The positive electrode film layer includes polycrystalline particles. The base coating includes first single-crystal particles, the volume distribution particle size Dv99 of which is less than or equal to 16 μm.

2. The battery cell according to claim 1, characterized in that, The volume distribution particle size Dv99 of the first single crystal particle is 5μm-16μm, and can be selected as 6μm-13μm.

3. The battery cell according to claim 1 or 2, characterized in that, The volume distribution particle size Dv50 of the first single crystal particle is 1μm-10μm, and can be selected as 1μm-6μm.

4. The battery cell according to any one of claims 1-3, characterized in that, The thickness of the base coating on one side is 7μm-30μm, and can be selected as 10μm-25μm.

5. The battery cell according to any one of claims 1-4, characterized in that, The volume distribution particle size Dv50 of the polycrystalline particles is 5μm-15μm; and / or, The volume distribution particle size Dv99 of the polycrystalline particles is 10μm-30μm.

6. The battery cell according to any one of claims 1-5, characterized in that, The positive electrode film also includes a second single crystal particle.

7. The battery cell according to claim 6, characterized in that, The volume distribution particle size Dv50 of the second single crystal particle is 1μm-10μm; and / or, The volume distribution particle size Dv99 of the second single crystal particle is 4μm-20μm.

8. The battery cell according to claim 6 or 7, characterized in that, Based on the total mass of the polycrystalline particles and the second single-crystal particles in the positive electrode film, the mass percentage of the polycrystalline particles is 50%-90%, and optionally 60%-80%.

9. The battery cell according to any one of claims 6-8, characterized in that, Based on the total mass of the polycrystalline particles and the second single-crystal particles in the positive electrode film layer, the mass percentage of the second single-crystal particles is 10%-50%, and can be selected as 20%-40%.

10. The battery cell according to any one of claims 1-9, characterized in that, The thickness of the positive electrode film on one side is 40μm-120μm, and can be selected as 70μm-110μm.

11. The battery cell according to any one of claims 1-10, characterized in that, The base coating includes a first positive electrode active material, and the positive electrode film includes a second positive electrode active material. The first positive electrode active material and the second positive electrode active material each independently include Li. a1 Ni x1 Co y1 M1 z1 M2 w1 O 2-b1 Wherein, M1 includes one or more of Mn and Al, and M2 includes one or more of Zr, B, Mg, Ti, W, Mo, Nb, Ta, Sr, Sb, and K; 0.8≤a1≤1.2, 0≤x1≤1, 0≤y1≤1, 0≤z1≤1, 0≤w1≤0.1, and -0.1≤b1≤0.

1.

12. The battery cell according to claim 11, characterized in that, The first positive electrode active material includes nickel, and based on the total molar number of transition metals in the first positive electrode active material, the molar percentage of nickel in the first positive electrode active material is 80%-96%; and / or The second positive electrode active material includes nickel. Based on the total number of moles of transition metals in the second positive electrode active material, the molar percentage of nickel in the second positive electrode active material is 80%-96%.

13. The battery cell according to any one of claims 1-12, characterized in that, When the battery cell is fully discharged, the compaction density of the positive electrode sheet is 3.4 g / cm³. 3 -3.65g / cm 3 .

14. An electrical appliance, characterized in that, The electrical device includes the battery cell according to any one of claims 1-13.